Structural control of mixed ionic and electronic transport in conducting polymers - Rivnay, Jonathan; Inal, Sahika; Collins, Brian A.; Sessolo, Michele; Stavrinidou, Eleni; Strakosas, Xenofon; Tassone, Christopher; Delongchamp, Dean M.; Malliaras, George G. (Nature communications, 2016)
Poly(3,4-ethylenedioxythiophene) doped with poly(styrenesulfonate), PEDOT:PSS, has been utilized for over two decades as a stable, solution-processable hole conductor. While its hole transport properties have been the subject of intense investigation, recent work has turned to PEDOT:PSS as a mixed ionic/electronic conductor in applications including bioelectronics, energy storage and management, and soft robotics. Conducting polymers can efficiently transport both holes and ions when sufficiently hydrated, however, little is known about the role of morphology on mixed conduction. Here, we show that bulk ionic and electronic mobilities are simultaneously affected by processing-induced changes in nano- and meso-scale structure in PEDOT:PSS films. We quantify domain composition, and find that domain purification on addition of dispersion co-solvents limits ion mobility, even while electronic conductivity improves. We show that an optimal morphology allows for the balanced ionic and electronic transport that is critical for prototypical mixed conductor devices. These findings may pave the way for the rational design of polymeric materials and processing routes to enhance devices reliant on mixed conduction. Conducting polymers are promising materials for applications including bioelectronics and soft robotics, but little is known about how morphology affects mixed conduction. Here, the authors show how bulk ionic/electronic transport is affected by changes in nano- and meso-scale structure in PEDOT:PSS films.